EFEKTIVITAS KOMBINASI MODEL PBL, TGT, DAN NHT DALAM MENINGKATKAN KETERAMPILAN KOLABORASI DAN BERPIKIR KREATIF DI SDN TELAGA BIRU 4 BANJARMASIN - Sella Maulida; Zain Ahmad Fauzi; Noorhapizah; Diani Ayu Pratiwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research is motivated by the researcher's initial findings, namely the low activity, collaboration skills, and creative thinking of students, this is caused by one-way learning, rare group learning, and less than optimal learning approaches. This study aims to analyze the increase in activity, collaboration skills, and creative thinking of students through the application of a combination of Problem Based Learning, Team Games Tournament, and Number Head Together models in Pancasila Education learning. This study uses a qualitative approach with the Classroom Action Research (CAR) method with research subjects being grade V students of SDN Telaga Biru 4. Data were collected through observation and written tests to obtain qualitative and quantitative data. The results of the study showed an increase in the activity of educators and students, as well as collaboration skills and creative thinking. Student activity increased from 44% to 88%, collaboration skills from 48% to 92%, and creative thinking from 32% to 84%. The completeness of learning outcomes also increased from 32% to 96%. These findings indicate that the combination of the three learning models is effective in improving the quality of the process and learning outcomes of Pancasila Education. This study recommends the application of innovative learning models as an alternative in developing active and meaningful learning.